2019
DOI: 10.1111/apa.14868
|View full text |Cite
|
Sign up to set email alerts
|

The use of abdominal imaging studies in children visiting emergency department was variable and unsystematic

Abstract: Aim: As imaging is used for various reasons in children with acute gastrointestinal complaints, we evaluated the indications and diagnostic yield of abdominal imaging, particularly ultrasound at emergency department (ED). Methods: Indications and imaging reports of consecutive children who had undergone abdominal imaging in general, surgical and paediatric EDs in the Tampere University Hospital, Finland, in 2015 were collected. Symptoms, clinical findings, imaging indications and findings were categorised and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Sub-group analysis within the 500+ group µg/g showed that for children where the index FC was related to a new diagnosis of IBD, they were more likely to have abnormal abdominal USSs than if they had an infectious GI condition or subsequent IBD. While abnormalities may be seen in USSs in children with infectious diarrhoea [26][27][28], abdominal USSs carried out on children presenting with diarrhoea, bleeding diarrhoea, or weight loss have positive findings in approximately 20% of cases [29]. In one further study, abnormal USS findings did not distinguish between functional and organic conditions [16].…”
Section: Discussionmentioning
confidence: 86%
“…Sub-group analysis within the 500+ group µg/g showed that for children where the index FC was related to a new diagnosis of IBD, they were more likely to have abnormal abdominal USSs than if they had an infectious GI condition or subsequent IBD. While abnormalities may be seen in USSs in children with infectious diarrhoea [26][27][28], abdominal USSs carried out on children presenting with diarrhoea, bleeding diarrhoea, or weight loss have positive findings in approximately 20% of cases [29]. In one further study, abnormal USS findings did not distinguish between functional and organic conditions [16].…”
Section: Discussionmentioning
confidence: 86%
“…Clinical practice guidelines discourage the use of AXR for the diagnostic workup of children with constipation due to its limited value, misleading nature, and radiation exposure [7][8][9][10][11][12][13][14]. AXR is an imperfect test for the assessment of constipation in children due to the absence of comparative radiologic normative data from children without constipation and the fact that symptoms may not correlate with the extent of faecal loading seen on the AXR or if other factors, such as air in the colon rather than the stool, may play a role in symptomatology.…”
Section: High Riskmentioning
confidence: 99%
“…While available data discourage the use of AXR for the evaluation of functional constipation in children due to its limited value, radiation exposure, as well as its possible misleading nature [7][8][9][10][11][12][13][14], a significant number of AXRs continue to be performed on children with constipation, particularly in the emergency department [15][16][17][18]. This has led to quality improvement projects that aim to reduce the number of abdominal X-rays performed in such children, with them showing promising results [19][20][21].…”
Section: Introductionmentioning
confidence: 99%